Space technologies and applications development in meeting SDGs challenges in Malaysia - Mohd Noor, Norzailawati; Mazlan, Hashim (2019)
Globally space technologies are updating every day, the usage of it have been explored with new applications has been established particularly to accommodate sustainable development goals (SDGs) mission nowadays. This study is partial taking an initiative to update a progress on space technologies in urban applications to date of 2019 in attending a challenge of SDGs implementation by Malaysia through goals 11 and 15. Many works has been reviewed throughout of Malaysia and found that Malaysia government is committed in addressing the sustainable issues for the betterment of society, economy and environment for present and future undertakings with Space technology usage is focusing more on geospatial remote sensing, GNSS and extending to GIS. However, the tune of country vision and mission recently influences a decision of space data usage. The constraint on financial, management and experts in accommodating space technologies trend compare to GIS, making the application of space technologies especially remote sensing in Malaysia for urban applications was consider not really well explored. Hence, it challenging for Malaysia surviving their SDGs mission with this upcoming space technologies development scenario.